PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA AUDIOVISUAL TERHADAP KETERAMPILAN MENYIMAK TEKS EKSPLANASI SISWA KELAS IX SMP NEGERI 7 PADANG - Febriyan, Reyvany; Nursaid*, Nursaid; Hafrison, Mohammad; Rasyid, Yulianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe and analyze the effect of the Problem Based Learning (PBL) model assisted by audiovisual media on students’ listening comprehension skills of explanatory texts. This research employed a quantitative approach using a quasi-experimental method with a one-group pretest-posttest design. The sample consisted of 31 ninth-grade students of SMP Negeri 7 Padang. The research instrument was an objective multiple-choice test based on three indicators: text structure, language use, and content comprehension.The results showed that the average score of students’ listening skills before treatment was 74.88, while after treatment it increased to 85.37. The normality test indicated that the data were normally distributed, and the homogeneity test showed that the data had homogeneous variance. Furthermore, the hypothesis test revealed that the tcount value (4.54) was higher than the ttable value (2.04) at the 0.05 significance level. Therefore, it can be concluded that the implementation of the Problem Based Learning model assisted by audiovisual media has a significant effect on students’ listening comprehension skills of explanatory texts.